Pure Economic Loss: Comparing Posner’s Idea of Economic Loss with the Treatment of Pure Economic Loss in English Common Law - Olusoga-Tinubi, Hannah (African Journal of Stability and Development (AJSD), 2018)
This paper studies pure economic loss in torts with the aim of determining how well the law of torts, as developed in English Common Law, is well adjusted to the economics principle of efficiency. The study attempts to measure the efficiency or otherwise of economic loss doctrine in English Common Law by comparing the treatment of pure economic loss in the English legal system with economic criteria developed by Richard Posner– a United States of America’s Court of Appeal Judge, jurist, economist, professor and major contributor in the field of Law and Economics. This comparative analysis reveals that the economic loss doctrine is in harmony with the principles of efficiency in Law and Economics. Using the French legal system as an example, this work finds out that a legal system’s treatment of pure economic loss may still be in harmony with the principles of efficiency without necessarily relying on economic loss doctrine. This conclusion is however without prejudice to the fact that the English legal system, by alluding to the principles of efficiency, is able to determine not only the reason for the existence of certain legal rules but also the effect of such legal rules in the society thereby maintaining an edge over some other legal systems which fail to take into account principle of efficiency